Fatal Pulmonary Embolism in the Setting of Immune Reconstitution Inflammatory Syndrome Attributed to Ovarian Tuberculosis. (September 2017) - Ugalde, Israel; Pirela, Daniela; Lo Presti, Saberio; Bilderback, Molly; Pirela, Andrés; Chan, Joseph
In developed countries, tuberculosis remains a health care challenge due to human immunodeficiency virus (HIV) and immigration from endemic regions. The Centers for Disease Control and Prevention reported 9557 new cases in 2015, with extrapulmonary involvement in 20.2% of the cases. We present a 33-year-old woman from Cape Town, South Africa, who developed abdominal pain and fever while working on a cruise ship. She sought medical where she underwent computed tomography of her chest, abdomen, and pelvis with findings suggestive of pulmonary tuberculosis and an 8.9-cm pelvic mass. HIV testing was positive and the patient was started on antiretroviral therapy. Bronchoscopy confirmed the presence of acid-fast bacilli, and she was started on rifampin, isoniazid, pyrazinamide, and ethambutol. She remained persistently febrile, raising suspicion for immune reconstitution inflammatory syndrome. However, despite empiric antibiotics, the patient remained persistently febrile, tachycardic, and on day 10 of admission she went into ventricular fibrillation and expired. Autopsy revealed an occlusive thrombus in the left main pulmonary artery in addition to necrotizing granulomata in multiple organs and bilateral tubo-ovarian abscesses. Postmortem cultures for were positive for Mycobacterium tuberculosis, all consistent with disseminated Mycobacterium tuberculosis . Although previous reports underscore the association between tuberculosis and hypercoagulability, the exact mechanism remains unknown. In this article, we report a case of disseminated tuberculosis complicated by bilateral tubo-ovarian abscesses with fatal pulmonary thrombus formation.